Analisis Kemampuan Pemahaman Relasional Matematis : Dampak Strategi Pembelajaran Index Card Match - Wulandari, Fitri; Rakhmawati, Rosida (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to determine (1) differences in the ability of relational understanding of mathematics of students who get learning with Index Card Match learning strategies with students who obtain conventional learning, (2) differences in the ability of mathematical relational understanding of students who have high, medium and low, (3) interaction of Index Card Match learning strategies and the level of interest in learners 'learning on the students' mathematical relational understanding abilities. The method used in this study is a quasi-experimental (Quasi Experimental Research). Hypothesis testing using two-way cell anava is not the same. Based on the results of the study it can be concluded (1) There is a difference in the ability of mathematical relational understanding of students who get learning with Index Card Match learning strategies with students who obtain conventional learning, (2) There are differences in the ability of students to have a high learning interest interest in learning is moderate, and interest in learning is low, (3) There is no interaction between Index Card Match learning strategies and the level of interest in learners 'learning on students' mathematical relational understanding abilities.